Uji Beda Pembiayaan Bermasalah pada Pembiayaan Mudharabah dan Musyarakah Bank Umum Syariah di Indonesia Selama Pandemi Covid 19 - Taudlikhul Afkar; Teguh Purwanto (ITB AAS INDONESIA Surakarta, 2021)
The test of the difference in problematic financing on mudaraba and musharaka financing is the purpose of this study because it is used to determine the implications of the COVID-19 pandemic in Islamic Commercial Banks of Indonesia. Quantitative research methods are the choice in explaining these differences by using paired sample t-test analysis, which was carried out with paired samples through two different events, namely before and during the covid 19 pandemic. Saturated samples were used in sampling as many as 14 Islamic Commercial Banks in Indonesia. The data is collected from the combined reports of Islamic Commercial Banks at the Financial Services Authority in time series. The results showed that non-performing financing that occurred in mudaraba financing before and during the pandemic experienced a significant difference with a downward trend, while non-performing financing in musharaka financing experienced a significant difference with an upward trend, meaning that during the COVID-19 pandemic it had an impact on changes in non-performing financing.